Isolation, Characterization and Evaluation of Mimosa pudica Seed Mucilage as Pharmaceutical Additives (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of this present work was to isolate, characterized, and evaluate the natural plant-basedpolysaccharides from the seeds of Mimosa pudica plant which belongs to family Mimosaceae. In pharmaceuticalindustries large number of excipients is used which are obtained from natural sources, mucilage is one ofthem. Mucilage and their derivatives are a group of polymers extensively used in pharmaceutical dosageforms. Materials and Methods: The fresh M. pudica seeds were collected from Botanical Garden GreaterNoida India. The plant was authenticated at the pharmacognosy department by a scientist at National Instituteof Science Communication and Information Resources (NISCAIR) Delhi. (Authentication voucher no.NISCAIR/RHMD/Consult/2019/3437-38) All other chemicals used were of analytical grade, and distilledwater was used throughout the experiments. M. pudica (family Mimosaceae), commonly known as sensitiveplant and widely used as herbal medicine in India, is widely available and has very low cost. It is diffuseunder shrub found widely in the tropical and subtropical parts of India. Seeds of M. pudica yield mucilage,which is composed of d-xylose and d-glucuronic acid. Mimosa seeds mucilage hydrates and swells rapidlyon coming in contact with water. The present investigation involved isolation of mucilage from M. pudicaseeds commonly known as chhui mui followed by phytochemical and physicochemical evaluation. Resultsand Discussion: The mucilage isolated from the seed of M. pudica will be useful as an excipient for oraldrug delivery systems as the results of phytochemical and physicochemical tests indicated the suitability ofmucilage for tablet dosage form as well as a suspending agent for suspension due to its flowability, weaklyacidic pH, swelling potential, and viscous in nature. The present study suggests that isolated mucilage fromthe seeds of M. pudica showed good flow properties which is suitable for a direct compression formulationand is non-irritating in nature to the mucosal membrane.